Role of Organizations in skill Development Program in India - Pandey, Dr Tarkeshwar (IJRDO - Journal of Applied Management Science, 2016)
Skill development and entrepreneurship efforts across the country have been highly fragmented so far. As opposed to developed countries, where the percentage of skilled workforce is between 60% and 90% of the total workforce, India records a low 5% of workforce (20-24 years) with formal vocational skills. There is a need for speedy reorganization of the ecosystem of skill development and entrepreneurship promotion in the country to suit the needs of the industry and enable decent quality of life to its population. Today, more than 20 Ministries/Departments run 70 plus schemes for skill development in the country. However, there are gaps in the capacity and quality of training infrastructure as well as outputs, insufficient focus on workforce aspirations, lack of certification and common standards and a pointed lack of focus on the unorganized sector. Recognizing the need and urgency of quickly coordinating the efforts of all concerned stakeholders in the field of Skill Development and Entrepreneurship, Government of India notified the formation of the Department of Skill Development and Entrepreneurship on 31st July, 2014 which subsequently led to the creation of the Ministry of Skill Development and Entrepreneurship on 10th Nov, 2014